Symmetric Functions of Roots of a Quadratic Equation

Let α and β be the roots of the quadratic equation ax\(^{2}\) + bx + c = 0, (a ≠ 0), then the expressions of the form α + β, αβ, α\(^{2}\) + β\(^{2}\), α\(^{2}\) - β\(^{2}\), 1/α^2 + 1/β^2 etc. are known as functions of the roots α and β.

If the expression doesn’t change on interchanging α and β, then it is known as symmetric. In other words, an expression in α and β which remains same when α and β are interchanged, is called symmetric function in α and β.

Thus \(\frac{α^{2}}{β}\) + \(\frac{β^{2}}{α}\) is a symmetric function while α\(^{2}\) - β\(^{2}\) is not a symmetric function. The expressions α + β and αβ are called elementary symmetric functions.

We know that for the quadratic equation ax\(^{2}\) + bx + c = 0, (a ≠ 0), the value of α + β = -\(\frac{b}{a}\) and αβ = \(\frac{c}{a}\). To evaluate of a symmetric function of the roots of a quadratic equation in terms of its coefficients; we always express it in terms of α + β and αβ.

With the above information, the values of other functions of α and β can be determined:

(i) α\(^{2}\) + β\(^{2}\) = (α + β)\(^{2}\) - 2αβ

(ii) (α - β)\(^{2}\) = (α + β)\(^{2}\) - 4αβ

(iii) α\(^{2}\) - β\(^{2}\) = (α + β)(α - β) = (α + β) √{(α + β)^2 - 4αβ}

(iv) α\(^{3}\) + β\(^{3}\) = (α + β)\(^{3}\) - 3αβ(α + β)

(v) α\(^{3}\) - β\(^{3}\) = (α - β)(α\(^{2}\) + αβ + β\(^{2}\))

(vi) α\(^{4}\) + β\(^{4}\) = (α\(^{2}\) + β\(^{2}\))\(^{2}\) - 2α\(^{2}\)β\(^{2}\)

(vii) α\(^{4}\) - β\(^{4}\) = (α + β)(α - β)(α\(^{2}\) + β\(^{2}\)) = (α + β)(α - β)[(α + β)\(^{2}\) - 2αβ]


Solved example to find the symmetric functions of roots of a quadratic equation:

If α and β are the roots of the quadratic ax\(^{2}\) + bx + c = 0, (a ≠ 0), determine the values of the following expressions in terms of a, b and c.

(i) \(\frac{1}{α}\) + \(\frac{1}{β}\)

(ii) \(\frac{1}{α^{2}}\) + \(\frac{1}{β^{2}}\)


Since, α and β are the roots of ax\(^{2}\) + bx + c = 0,
α + β = -\(\frac{b}{a}\) and αβ = \(\frac{c}{a}\)

(i) \(\frac{1}{α}\) + \(\frac{1}{β}\)

= \(\frac{α + β}{αβ}\) = -b/a/c/a = -b/c

(ii) \(\frac{1}{α^{2}}\) + \(\frac{1}{β^{2}}\)

= α^2 + β^2/α^2β^2

= (α + β)\(^{2}\) - 2αβ/(αβ)^2

= (-b/a)^2 – 2c/a/(c/a)^2 = b^2 -2ac/c^2

11 and 12 Grade Math 

From Symmetric Functions of Roots of a Quadratic Equation to HOME PAGE

Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.

New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.